Borderline personality disorder: current drug treatments and future prospects - Olabi, Bayanne (SAGE Publications, 2010)
Individuals with borderline personality disorder (BPD) suffer from marked affective disturbance, an unstable sense of self, difficulty in interpersonal relationships and heightened impulsivity, leading to high rates of self-harm and suicide. Patients are often refractory to treatment and are at high risk for acute or dangerous presentations, with a serious impact on mental health services. There has been much debate on the effectiveness of pharmacotherapy in treating different facets of the psychopathology of the disorder. Several guidelines recommend the use of antidepressant agents, mood stabilizers for affective dysregulation and impulsive-behavioural dyscontrol, and antipsychotics for cognitive-perceptual symptoms. However, concerns have recently been raised regarding the strength of evidence for these treatment recommendations in BPD. Here, we review the evidence for efficacy of the main psychotropic medications used in BPD, drawing, in particular, on evidence from randomized controlled trials and meta-analyses. Overall, meta-analysis provides little evidence to support the use of antidepressant medication in BPD outside episodes of major depression. However, there is evidence for the use of both mood stabilizers and antipsychotic medications for the treatment of specific aspects of the disorder. Most existing studies have been conducted on small numbers of patients, and there is a requirement for further large-scale trials to substantiate these findings. In addition, given the limitations of current pharmacological treatment of BPD, there is a pressing need to investigate potential new therapeutic targets, including neuropeptides, such as the opioids and vasopressin, and drugs targeted at ameliorating the biological effects of early life stress.